Giant dielectric response and relaxation behavior in (Tm + Ta) co-doped TiO2 ceramics. Issue 8 (10th February 2022) - Fan, Jiangtao; Chen, Yimeng; Long, Zhen; Tong, Liping; He, Gang; Hu, Zhanggui
Abstract : Here we report the synthesis of (Tm + Ta) co-doped TiO2 ceramic by SSR method. Grain effect (EPDD), grain boundary effect (IBLC) and electrode effect all contributes to the colossal permittivity (CP) in (Tm + Ta) codoped TiO2 ceramics. Abstract : Dielectric materials with huge dielectric constants are attracting attention due to the growing demand for microelectronics and high energy-storage devices. In this work, Tm + Ta co-doped TiO2 ceramics were prepared by a solid-state reaction (SSR) method, and the microstructure and dielectric behavior were investigated. A ultrahigh permittivity ( ε r ∼ 2.26 × 10 4 ) and very low loss (tan  δ ∼ 0.011) are achieved at 1 kHz for (Tm0.5 Ta0.5 )0.01 Ti0.99 O2 ceramics. XPS analysis confirms that the high dielectric constant and low dielectric loss are attributed to the electron pinned defect dipole (EPDD) response formed by the coupling of Ti 3+ and oxygen vacancies. In addition, impedance analysis and frequency dependent dielectric constant under a DC bias indicate that the presence of the internal barrier layer capacitance (IBLC) response and electrode response at low to medium frequencies (<10 6 Hz) also contribute significantly to the dielectric constant. The findings reported in this work provide valuable insights into the simultaneous realization of a low dielectric loss and high permittivity in Tm + Ta co-doped TiO2 ceramics and other related dielectric ceramics.